The problem of transition and reintegration of East and Central Europe: conceptual remarks and empirical problems - Andreas P. Cornett (European Regional Science Association (ERSA), 1998)
Abstract: Eight years after the fall of the Berlin Wall and the Iron Curtain economic and political cleavages are still visible in Europe. With respect to social and economic transition the saliency of the problems seem to increase, as the efforts to solve the problems become the common business of governments and international organizations. Regional economic and political integration have significant impacts on this process, namely through the European Union programs for restructuring and development. The purpose of this paper is to analyze the main problems in the process of transition and reintegration has to so overcome from a theoretical and conceptual point of view. The theoretical anchors political and economic theories of regional integration. After a period with declining attention, regional integration has again become topic in various parts of the world. Concepts of integration are still pivotal in Europe, partly regarding the internal development of the European Union, partly as a framework of cooperation between the EU and the rest of Europe. Based on the analysis of the concepts of Regional Economic Cooperation in Europe, the links between international economic integration and internal development are analyzed. The relationship between makcroeconomic integration and the necessary of providing instruments to cover specific areas or sector from significant adverse effects of this process is given special attention in the analysis.. This part of the analysis will focus on the needs for restructuring of existing EU-policies to meet the challenges of the next enlargements. The theoretical concepts will be used for a principal evaluation of the needs for a future regional policy for an enlarged community. The process of transition and recovery in East Europe has been challenged not only by the regained influence of traditional political groups in East Europe but also through the reluctance of the EU to open their markets in sectors where the former CMEA-countries are competitive. To avoid further drawbacks it seems necessary to establish a self sustainable economic system able to handle external (i.e. the process of enlargement) as well as internal (i.e. the structural funds) demands for restructuring. The first precondition is the opening of western markets. The second is to provide a reliable regime for development and knowledge transfer. Last but not least, the paper stress' the need to establish a reasonable framework for cooperation until the East and Central Europe can participate on equal terms in the mainstream of European Integration, and to handle the different waves of membership negotiations in a reliable way. Keywords: Reintegration, Regime for transition, Concepts of structural adaptation and integration.
Keywords: 330